Strengths finder 2.0 - Rath, Tom, 1975- (New York : Gallup Press, 2007)
To help people uncover their talents, Gallup introduced the first version of its online assessment, StrengthsFinder, in the 2001 management book Now, Discover Your Strengths. The book has spent more than five years on bestseller lists and ignited a global conversation, while StrengthsFinder has helped millions discover their top five talents. In StrengthsFinder 2.0, Gallup unveils the new and improved version of its popular assessment and much more. Loaded with hundreds of strategies for applying your strengths, this new book and accompanying website will change the way you look at yourself-- and the world around you--forever.
Finding your strengths : an introduction -- Applying your strengths : the 34 themes and ideas for action. Achiever ; Activator ; Adaptability ; Analytical ; Arranger ; Belief ; Command ; Communication ; Competition ; Connectedness ; Consistency ; Context ; Deliberative ; Developer ; Discipline ; Empathy ; Focus ; Futuristic ; Harmony ; Ideation ; Includer ; Individualization ; Input ; Intellection ; Learner ; Maximizer ; Positivity ; Relator ; Responsibility ; Restorative ; Self-assurance ; Significance ; Strategic ; Woo -- VFAQ (very frequently asked question) -- Learn more.
Packet inserted on p. [3] of cover contains card with access code to the StrengthsFinder 2.0 assessment, program, and website.
Includes bibliographical references.
Keywords: Executive ability; Ability; Performance; Success in business; Conduct of life; Aptitude; Achievement; Self Assessment (Psychology); Leadership